The precision of 12-month-old infants’ link between language and categorization predicts vocabulary size at 12 and 18 months - Ferguson, Brock; Havy, Mélanie; Waxman, Sandra R. (Frontiers in Psychology, 2015)
Infants’ initially broad links between language and object categories are increasingly tuned, becoming more precise by the end of their first year. In a longitudinal study, we asked whether individual differences in the precision of infants’ links at 12 months of age are related to vocabulary development. We found that, at 12 months, infants who had already established a precise link between labels and categories understood more words than those whose link was still broad. Six months later, this advantage held: At 18 months, infants who had demonstrated a precise link at 12 months knew more words and produced more words than did infants who had demonstrated a broad link at 12 months. We conclude that individual differences in the precision of 12-month-old infants’ links between language and categories provide a reliable window into their vocabulary development. We consider several causal explanations of this relation.